A Tandem Solar Biofuel Cell: Harnessing Energy from Light and Biofuels. (24th November 2020) - Riedel, Marc; Höfs, Soraya; Ruff, Adrian; Schuhmann, Wolfgang; Lisdat, Fred
Abstract: We report on a photobioelectrochemical fuel cell consisting of a glucose‐oxidase‐modified BiFeO3 photobiocathode and a quantum‐dot‐sensitized inverse opal TiO2 photobioanode linked to FAD glucose dehydrogenase via a redox polymer. Both photobioelectrodes are driven by enzymatic glucose conversion. Whereas the photobioanode can collect electrons from sugar oxidation at rather low potential, the photobiocathode shows reduction currents at rather high potential. The electrodes can be arranged in a sandwich‐like manner due to the semi‐transparent nature of BiFeO3, which also guarantees a simultaneous excitation of the photobioanode when illuminated via the cathode side. This tandem cell can generate electricity under illumination and in the presence of glucose and provides an exceptionally high OCV of about 1 V. The developed semi‐artificial system has significant implications for the integration of biocatalysts in photoactive entities for bioenergetic purposes, and it opens up a new path toward generation of electricity from sunlight and (bio)fuels. Abstract : A photobioelectrochemical tandem cell is presented in which two photoelectrodes have been functionally coupled with two biocatalysts for supplying the light‐driven reaction with charge carriers from glucose conversion. The cell allows the generation of electricity from biofuels and light with a high open‐circuit voltage of 1 V.